Commitment follows beliefs: A configurational perspective on operations managers' commitment to practice adoption. Issue 4 (21st December 2020) - Arellano, Maricela C.; Meuer, Johannes; Netland, Torbjørn H.
Abstract: Companies that seek to improve their operational performance by adopting new practices often report disappointing adoption rates. The literature concerning practice adoption has tended to focus on efficacy and legitimacy drivers at the organizational level. However, there exists convincing evidence that practice adoption largely depends on the commitment of those managers involved in the adoption of a given practice. Thus, we investigate what prompts operations managers to commit to practice adoption. We draw on the theory of planned behavior to explore the cognitive foundations of 76 operations managers' commitment to new operational practices. Using fuzzy‐set qualitative comparative analysis, we identify three belief configurations associated with high levels of commitment—"the Follower, " "the Pragmatist, " and "the Reformer." We contribute a behavioral operations perspective to the literature on practice adoption by providing an individual‐level and configurational view of managerial commitment to change.